2004
DOI: 10.1254/jphs.fp0040424
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Acts Through Brain Serotonergic Mechanisms to Induce Thermal Effects

Abstract: Abstract. The present study was attempted to investigate the effect of puerarin, an isoflavone compound isolated from Pueraria lobata, on both the basal body temperature and pyrogenic fever in unanesthetized, restrained rats. Intraperitoneal administration of puerarin or crude extracts of Pueraria lobata elicited hypothermia. Direct administration of a small amount of puerarin into the lateral cerebral ventricle produced the same extent of hypothermia. Systemic or central administration of puerarin causes a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 20 publications
3
24
0
Order By: Relevance
“…The experimental group, group C, received N. lobata leaves extract. This group had an antipyretic effect evident also 30 minutes after administration with a maximum antipyretic effect of 0.81 o C. As it has been described before [12], isoflavones have antipyretic effects. Kerr and collaborators [4] had isolated 12 different flavonoides from N. lobata and it is suggested that these could be some of the components responsible for N. lobatas´ antipyretic effect.…”
Section: Discussionsupporting
confidence: 76%
“…The experimental group, group C, received N. lobata leaves extract. This group had an antipyretic effect evident also 30 minutes after administration with a maximum antipyretic effect of 0.81 o C. As it has been described before [12], isoflavones have antipyretic effects. Kerr and collaborators [4] had isolated 12 different flavonoides from N. lobata and it is suggested that these could be some of the components responsible for N. lobatas´ antipyretic effect.…”
Section: Discussionsupporting
confidence: 76%
“…Ohwi (Chueh et al, 2004). This medicinal herb has been demonstrated to have effects on treatment of fever (Zhou et al, 1995;Chueh et al, 2004), liver diseases (Keung and Vallee, 1993;Overstreet et al, 1996) and cardiovascular diseases (Fang, 1980;Chai et al, 1985;Song et al, 1988;Fan et al, 1992;Wang et al, 1994). In China, P. lobata is also used as a health supplement for reducing risk factors of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Puerariae radix contains several isoflavonoids, including puerarin, daidzin, daidzein, formononetine and their C-and O-glycosides (Prasain et al, 2003). These compounds have been associated with antioxidant, antidipsotropic, and other pharmacological activities (Chueh et al, 2004;Lee, 2004). It was reported recently that daidzin and daidzein offer protection against carbon tetrachloride-, D-GalN-and t-butyl hydroperoxide-induced hepatotoxicity in vitro (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%